THE LENGTH-WEIGHT RELATIONSHIP AND CONDITION FACTOR OF FISH SPECIES IN DADIN-KOWA RESERVOIR GOMBE STATE, NIGERIA - YERIMA, R; BOLORUNDURO, P.I; SULEIMAN, B; UMAR, D.M; BAYERO, U (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The length-weight relationship and condition factor of eleven resident fish species belonging to the eleven families in Dadin-Kowa reservoir were studied. Fish were sampled from three stations using conventional fishing gears from landing sites of the reservoir. The fish samples were identified using standard descriptions keys. A total of 283 individual fish were sampled, with one (1) species per family from the reservoir. The families include Mormyridae, Bagridae, Cichlidae, Mochokidae, Alestidae, Cyprinidae, Clariidae and Claroteidae, Malapteruridae, Polypteridae and Schilbeidae. The weight-length relationship varied within the ranges of 7 – 40cm and 100 – 500g for total length and body weight respectively. The regression coefficient b ranged between 1.034 – 2.124, and the intercept was within the range of 0.276 – 0.932. There was high positive correlation between the length and weight, with Chrysichthys auratus longifilis having the highest (r = 0.98) and the least in Mormyrus rume (Mormyridae ) with r value of 0.41. The condition factors of representative fish species showed the highest mean condition factor of 8.00±1.31 in Malapterurus minjiriya while Mormyrus rume had the least (2.98±0.33). This indicates that the fish species in this study showed good physiological state and health condition.